Coastal wetland management as a contribution to the US National Greenhouse Gas Inventory. Issue 12 (December 2018) - Crooks, Stephen; Sutton-Grier, Ariana; Troxler, Tiffany; Herold, Nathaniel; Bernal, Blanca; Schile-Beers, Lisa; Wirth, Tom
Abstract The IPCC 2013 Wetlands Supplement provided new guidance for countries on inclusion of wetlands in their National GHG Inventories. The United States has responded by including managed coastal wetlands for the first time in its 2017 GHG Inventory report along with an updated time series in the most recent 2018 submission and plans to update the time series on an annual basis as part of its yearly submission to the United Nations Framework Convention on Climate Change (UNFCCC). The United States followed IPCC Good Practice Guidance when reporting sources and sinks associated with managed coastal wetlands. Here we show that intact vegetated coastal wetlands are a net sink for GHGs. Despite robust regulation that has protected substantial stocks of carbon, the United States continues to lose coastal wetlands to development and the largest loss of wetlands to open water occurs around the Mississippi Delta due mostly to upstream changes in hydrology and sediment delivery, and oil and gas extraction. These processes create GHG emissions. By applying comprehensive Inventory reporting, scientists in the United States have identified opportunities for reducing GHG emissions through restoration of coastal wetlands that also provide many important societal co-benefits. Managed coastal wetlands have been included for the first time in the US Greenhouse Gas Inventory. Intact vegetated coastal wetlands are shown to represent a net greenhouse gas sink, but these are being lost to development, despite robust regulation, causing emissions.